Development of Multiliteration and Higher Order Thinking Skills Through Integrated Learning - Kurniasih Kurniasih (Universitas Sebelas Maret, 2019)
This paper aims to describe integrated learning as a learning approach, which is suggested to be applied in order to develop multiliteration and higher order thinking skills. Multiliteration and higher order thinking skills are needed and must be mastered by the community so that they can actively participate in the 21st century civilization. In this context, education or in its operation is learning to be challenged to be able to develop skills. Based on the literature study, it was concluded that to develop multiliteration and higher order thinking skills, one approach that needs to be applied is the integrated learning approach. There are two things that need to be considered in the application of integrated learning. First, the teacher should formulate learning objectives to develop cognitive process skills at levels C2 through C6. Second, in implementing integrated learning, the teacher ideally applies learning models such as: discover, inquiry, problem based learning, project based learning, cooperative learning models, etc.